Correlation Analysis Between Multi-Drug Resistance Phenotype and Virulence Factor Expression of Clinical Pseudomonas aeruginosa - Wenli Xu; Runcheng Zhou; Jingwei Pan; Zhuangcong Liu; Xuyu Huang; Yueqiao Lin; Nan Li; Kecan Chen; Wenbo Sun; Yi Deng; Anping Yang; Xin Chen (Current Issues in Molecular Biology)
Pseudomonas aeruginosa (PA), as a common pathogen of nosocomial infections, has been experiencing an increasing rate of drug resistance with the widespread use and abuse of antimicrobial drugs. High-drug-resistance and high-virulence phenotypes are two distinctive features of the strong pathogenicity of multi-drug-resistant PA. Exploring the characterization of virulence factor expression and its relationship with the multi-drug resistance phenotype is essential to reduce the further development of resistance as well as a high standard of infection prevention and control. A total of 50 PA isolated from clinical practice were collected. The Kirby-Bauer  test was used for drug-sensitive screening, and the results showed that 16 strains were resistant and 16 strains were sensitive. The drug resistance rate of multi-drug-resistant PA against cefepime, cefazolin, ampicillin, and imipenem was up to 100%. The multi-drug-resistant groups were superior in producing pyocyanin and forming biofilm to the sensitive groups. The distribution of isolates with different swarming motility capacities and elastase levels did not show pronounced differences among the multi-drug-resistant and sensitive groups. In addition, biofilm formation was moderately associated with imipenem resistance. Among the strains with strong virulence factor expression, the gene bands showed little difference, suggesting that the gene is highly homologous. The virulence factor matrix analysis showed that there were different degrees of correlation among the 4 virulence factors. The correlation between multidrug-resistant PA and virulence factor expression is complex. PA, which were good at producing pyocyain and forming biofilm, were highly resistant to cephalosporins, beta-lactams and carbepenems; hence, such drugs are not proper for anti-infective treatment in clinics.